The Effects of Music Interventions on Children's Pain Severity and Anxiety during Dressing Changes in Iraq: A Randomized Controlled Trial - Shawq, Adraa Hussein; Al-Musawi, Khatam Matsher; Kalel, Myasar Jasim; Mahmod, Ahmed Ali (Jurnal Keperawatan Soedirman, 2025)
Daily dressing changes cause distress and pain for victims of burn injuries. The study aimed to determine the effect of music in reducing the pain and anxiety of thermally burned children during routine dressing changes. This quantitative study employed a randomized controlled trial design. The participants comprised 80 children at the Specialized Burns Hospital, in Baghdad, Iraq who were divided into two groups. The intervention group were exposed to three generic musical pieces (children’s music, nature sounds, and classical music) for 10-15 minutes. The researchers used the Objective Pain Scale, State-Trait Anxiety Inventory, and physiological parameters to measure the children’s responses immediately before the dressing change and five minutes after, over seven days. The paired t-test and independent t-test were used to compare the means between the control and intervention groups. The mean values for the pain, anxiety, and physiological parameters before the procedure in both groups showed no significant differences (p > 0.01). The intervention group revealed significant statistical differences after being played music in all study parameters for pre- and post-dressing (p < 0.01), except for the blood pressure parameter. The music intervention alleviated children’s pain, anxiety, respiration, and pulse measurements when undergoing dressing changes.